2016
DOI: 10.1111/aman.12598
|View full text |Cite
|
Sign up to set email alerts
|

Writing Irataba: On Representing Native Americans on Wikipedia

Abstract: Wikipedia, the online encyclopedia that anyone can edit, is simultaneously an experiment in anarchic knowledge production and a realization of the long dream of modernity: storing all human knowledge. It is also a battleground for the politics of representation and for creating and circulating realities and "Wikialities." I ethnographically describe how Wikipedians, most of whom are white Anglo-Americans, negotiate the representation of Native Americans as objects of encyclopedic knowledge and how the sins of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Aqueles que acessam a Wikipédia apenas para ler artigos tendem a não se dar conta de como ela é um meio intertextual (Hansen, 2016), com diversas metapáginas para cada artigo enciclopédico. Assim, por exemplo, ao consultarmos o artigo "Antropologia" na Wikipédia lusófona (Antropologia, 2023), encontramos, no canto superior esquerdo da tela, ao lado da aba Artigo, uma aba que nos direciona à página de discussão sobre o artigo.…”
Section: Etnografando Práticas Textuais Onlineunclassified
“…Aqueles que acessam a Wikipédia apenas para ler artigos tendem a não se dar conta de como ela é um meio intertextual (Hansen, 2016), com diversas metapáginas para cada artigo enciclopédico. Assim, por exemplo, ao consultarmos o artigo "Antropologia" na Wikipédia lusófona (Antropologia, 2023), encontramos, no canto superior esquerdo da tela, ao lado da aba Artigo, uma aba que nos direciona à página de discussão sobre o artigo.…”
Section: Etnografando Práticas Textuais Onlineunclassified
“…It is not edited by historians either. Thus, in theory, it holds the potential to undermine dominant perceptions about what is historically important (Hansen, 2016). Yet, the continued prominence of national ideologies and specific political agendas in deletion decision making suggests that the same hegemonic forces that shape the construction of national histories persist even on user-generated encyclopedias.…”
Section: Wikipedia Editors and National Ideologymentioning
confidence: 99%
“…Hargittai and Shaw, 2015; Konieczny and Klein, 2018) and racial inequalities (e.g. Deumert, 2014; Hansen, 2016) that shape the content entries and creators’ identities. Other studies have found significant differences between distinct versions both in terms of content and in terms of the underlying infrastructure of the platform (Androutsopoulos, 2010; Deumert, 2014; Mamadouh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…First, writing in digital spaces is a learning tool, expanding the knowledge and skills students generate in classroom contexts. The communal and shared space of the digital world is a means for students to engage in cooperative learning and sharpen writing, research, and collaborative skills (Di Lauro & Johinke, 2017;Evenstein Sigalov & Nachmias, 2017;Johinke & Di Lauro, 2020;McDowell, 2017;O'Sullivan, 2016;Zou et al, 2020). At the undergraduate level, digital spaces may be among the few spaces in which students can undergo peer review (Cummings, 2020;Johinke, 2020;Johinke & Di Lauro 2020).…”
Section: Review Of the Literaturementioning
confidence: 99%